(untitled) (International Journal of Biology and Chemistry, 2024)
In this research palladium(II) chloride, PdCl2, reacts with (4ʹ-bromobiphenyl-4-yl)diphenylphosphine compound, Br(C6H4)2P(C6H5)2, to give trans-PdCl2L2 [L: Br(C6H4)2P(C6H5)2] complex. trans-dichloro bis(4ʹ-bromobiphenyl-4-yl)diphenylphosphine palladium(II) complex has been characterized by elemental analysis, FT-IR, 1H, 31P and 13C NMR. The catalytic performance of this complex has been rigorously evaluated and compared in the context of Suzuki-Miyaura and Mizoroki-Heck coupling reactions. It is noteworthy that under specific optimal conditions, including solvent type, base type, base quantity, catalyst quantity, and temperature, this complex serves as an efficient and suitable catalyst for the synthesis of biphenyl aryl halide derivatives. The resulting yield in these processes strongly supports the efficacy of this complex as a catalyst.